2011
DOI: 10.1002/chem.201101233
|View full text |Cite
|
Sign up to set email alerts
|

Can a Metal–Metal Bond Hop in the Fullerene Cage?

Abstract: Endohedral metallofullerenes (EMFs) are novel derivatives of fullerenes that can encapsulate metal atoms or clusters in their inner space.[1] Owing to their extraordinary properties attributed to significant electron transfer from the metal atoms to the fullerene cage, [2] EMFs have attracted wide interests since the discovery of fullerenes.[3] For instance, lanthanide metallofullerenes have been suggested for use as encapsulated contrasting agents for magnetic resonance imaging. [4] In EMFs, the internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 59 publications
6
64
0
Order By: Relevance
“…The computed 13 C chemical shis and intensities are 126.55 ppm (C1 intensity 1), 134.36 ppm (C3, intensity 6), 135.51 ppm (C2, intensity 3), 140.72 ppm (C5, intensity 3), and 141.01 ppm (C4, intensity 6), which agree very well with the experimental data ( Table 4) and those predicted by Yang et al 23 All the experimental data showed that Lu 2 @C 76 (T d ) has T d symmetry, 22 while our computations and those by Yang et al 23 showed that its lowest-energy isomer has C 2 symmetry. There are ve kinds of carbon atoms (points C1, C2, C3, C4, C5) in the patch, thus, 13 C NMR spectrum should have ve peaks.…”
Section: Nmr Spectrumsupporting
confidence: 88%
“…The computed 13 C chemical shis and intensities are 126.55 ppm (C1 intensity 1), 134.36 ppm (C3, intensity 6), 135.51 ppm (C2, intensity 3), 140.72 ppm (C5, intensity 3), and 141.01 ppm (C4, intensity 6), which agree very well with the experimental data ( Table 4) and those predicted by Yang et al 23 All the experimental data showed that Lu 2 @C 76 (T d ) has T d symmetry, 22 while our computations and those by Yang et al 23 showed that its lowest-energy isomer has C 2 symmetry. There are ve kinds of carbon atoms (points C1, C2, C3, C4, C5) in the patch, thus, 13 C NMR spectrum should have ve peaks.…”
Section: Nmr Spectrumsupporting
confidence: 88%
“…(S3), the nearest space between C 60 and rutile (1 1 0) surface is measured as 2.52 Å. And the CÀC bond length of C 60 is 1.39 and 1.44 Å, respectively, corresponding with our recently reports [35][36][37]. The binding energy (4.17 eV) of C 60 and rutile (1 1 0) is larger than that of graphene and rutile (1 1 0) in the neutral state.…”
Section: Modeling Of C 60 /Rutile (1 1 0) Compositesmentioning
confidence: 99%
“…[V] [35] whereas the non-IPR C s (17490)-C 76 cage, with two APPs, is the cage selected by clusters that transfer six electrons (M 3 N, La 2 ). Moreover,t he comparative studies of …”
Section: Electrochemical Studiesmentioning
confidence: 99%
“…[32] Nevertheless,t hough several theoretical and spectroscopics tudies have been devoted to the characterization of T d -C 76 ,b esides af unctionalized C s -(T d -C 76 (CF 3 ) 12 ), [33] Lu 2 @T d -C 76 is the only discovered species so far. [32,[34][35][36] Moreover,t he studies of Lu 2 @T d -C 76 did not provide ad etailed structural analysis because of the lack of unambiguous single-crystal X-ray characterization. Thus, furthers tudy is very necessary to reveal the structuralfeatures of the T d -fullerenes.…”
Section: Introductionmentioning
confidence: 98%